Five phase permanent magnet synchronous motor decoupled model with dual frame frequency adaptive flux observer. (December 2020) - Long, Linghui; Sun, Tianfu; Liang, Jianing
Abstract: In this paper, a five-phase permanent magnet synchronous motor (five phase PMSM) decoupled model is proposed to avoid the inaccuracy and computational complexity of conventional five phase PMSM model, which always ignores the mutual inductance between the fundamental and harmonic flux linkage. Unlike traditional inductances based five phase PMSM model, the proposed five phase PMSM decoupled model is built based on flux linkages. Moreover, to improve the accuracy of the proposed five phase PMSM decoupled model for model predictive control, a duel frame-frequency adaptive flux observer (DF-FAFO) is proposed, which can estimate both fundamental flux linkage and 3rd harmonic flux linkage online. The DF-FAFO can estimate the flux linkages accurately and minimize the unwanted harmonic ripple even if the torque is changed. The effectiveness of the proposed decoupled model and the DF-FAFO is demonstrated by simulations.